Targeting ATAD3A Phosphorylation Mediated by TBK1 Ameliorates Senescence‐Associated Pathologies - Yujiao He; Yanchen Liu; Mingyue Zheng; Yuxiu Zou; Mujie Huang; Linsheng Wang; Ge Gao; Zhongjun Zhou; Guoxiang Jin (Advanced Science)
Abstract Targeting cellular senescence, one of the hallmarks of aging and aging‐related pathologies emerges as an effective strategy for anti‐aging and cancer chemotherapy. Here, a switch from TBK1‐OPTN axis to TBK1‐ATAD3A axis to promote cellular senescence is shown. Mechanically, TBK1 protein is abnormally activated and localized to the mitochondria during senescence, which directly phosphorylates ATAD3A at Ser321. Phosphorylated ATAD3A is significantly elevated in cellular senescence as well as in physiological and pathological aging and is essential for suppressing Pink1‐mediated mitophagy by facilitating Pink1 mitochondrial import. Inhibition of ATAD3A phosphorylation at Ser321 by either TBK1 deficiency or by a Ser321A mutation rescues the cellular senescence. A blocking peptide, TAT‐PEP, specifically abrogating ATAD3A phosphorylation, results in elevated cell death by preventing doxorubicin‐induced senescence, thus leading to enhanced tumor sensitivity to chemotherapy. TAT‐PEP treatment also ameliorates various phenotypes associated with physiological aging. Collectively, these results reveal the TBK1‐ATAD3A‐Pink1 axis as a driving force in cellular senescence and suggest a potential mitochondrial target for anti‐aging therapy.